Les inégalités d’accès aux ressources urbaines dans les franges périphériques de Belo Horizonte (Brésil) : quelles évolutions ? - Eugênia Viana Cerqueira (EchoGéo)
This paper aims at evaluating inequalities in access to urban resources the Metropolitan Region of Belo Horizonte in the light of the recent socio-spatial evolutions of the peripheral spaces. First, the analysis of resources relative density helps identifying their spatial distribution in the MRBH. Furthermore, the exploitation of the latest household-travel survey and a set of qualitative interviews emphasize that, despite the diversification process experienced in the peripheries, the inequalities in access to urban resources are still pronounced. The mobility behavior of the upper classes is shaped by their individual choices, whilst the poorest are still forced to develop strategies to access urban resources.